2014
DOI: 10.1016/j.esd.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in financing that drive cost parity for long-term electricity sustainability: An assessment of Italy, Europe's fastest growing solar photovoltaic market

Abstract: copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their personal website or institutional repository. Authors requiring further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Hence LCOE of individual technologies is an important indicator to assess cost parity, however it has to be contextualized in order to be meaningful [16,17,19,24,25,29,30,33,42,44,[64][65][66][67][68][69][70][71][72][73][74][75][76].…”
Section: Cost Paritymentioning
confidence: 99%
“…Hence LCOE of individual technologies is an important indicator to assess cost parity, however it has to be contextualized in order to be meaningful [16,17,19,24,25,29,30,33,42,44,[64][65][66][67][68][69][70][71][72][73][74][75][76].…”
Section: Cost Paritymentioning
confidence: 99%
“…Third, other studies conducted the economic analysis of the solar PV system outside of the U.S., especially in EU, by considering solar incentives (Ameli, Kammen 2014;Antonelli, Desideri 2014;Frondel et al 2010;Hass et al 2011;Laleman, Albrecht 2014). Ameli and Kammen (2014) developed a financing tool based on a pollution abatement methodology in order to examine options to bridge the cost gap between solar PV and other energy generation technologies in Italy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ameli and Kammen (2014) developed a financing tool based on a pollution abatement methodology in order to examine options to bridge the cost gap between solar PV and other energy generation technologies in Italy. The results showed that well-designed Property Assessed Clean Energy (PACE) loan program, as an alternative to subsidy programs (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It allows cost comparisons, in current monetary units, of a kWh of electricity generated by PV systems with other sources of electricity [16]. Therefore, LCOE is calculated by dividing the cumulative PV system costs by the energy produced over its lifetime, as shown in the following equation [80]:…”
Section: Pv Electricity Cost Production Analysismentioning
confidence: 99%
“…However, the present Italian regulatory framework allows PV systems to take advantage of net metering, facilitating energy self-consumption. In this context, it is essential to assess whether unsubsidized electricity production from PV plants remains economically convenient, in order to provide a real measure of the competitiveness of photovoltaic technologies [16].…”
Section: Introductionmentioning
confidence: 99%